"Hemispheric Postcolonialism: Black Female Sexuality and Slavery in the Americas". Issue 9 (September 2016) - Shinn, Christopher A.
Abstract: Building on what Günter H. Lenz describes as the "always two‐directional processes of transculturation, " this piece brings together two classic works, Gayl Jones's Corregidora and Carlos Diegues's Brazilian film, Xica da Silva (1975), specifically addressing the hemispheric connections in cross‐cultural literary and cinematic representations of black female sexuality, colonialism and slavery in the Americas. The essay presents a critical comparison of the legacy of slave concubinage and black female resistance, noting how Jones's Corregidora helps to undermine the Brazilian myth of racial democracy, while Xica da Silva deepens Gayl Jones's Pan‐African vision of the quilombos, or maroon societies, and problematizes sexuality by magnifying the complex mix of abjection and desire, which deeply engages Jones's novel. By furthering an already existing discussion yet promoting a new critical paradigm for a hemispheric postcolonialism, this work seeks to fortify the nexus of Africana Studies, Comparative American Studies and Hemispheric Studies, but with a distinct postcolonial focus on the historic and cultural intersections of U.S. and Latin America, working within the purview of postcolonial studies in particular.